Efficient charge separation and visible-light response in bilayer HfS2-based van der Waals heterostructures. Issue 34 (23rd May 2018) - Wang, Biao; Luo, Xukai; Chang, Junli; Chen, Xiaorui; Yuan, Hongkuan; Chen, Hong
Abstract : In this work, we employ hybrid density functional theory to investigate HfS2 -based van der Waals (vdW) heterojunctions for highly efficient photovoltaic and photocatalytic applications. Abstract : Two-dimensional (2D) hafnium disulfide (HfS2 ) has been synthesized and is expected to be a promising candidate for photovoltaic applications, and at the same time the hexagonal BN sheet (h-BN) and graphene-like C3 N4 sheet (g-C3 N4 ) have also been fabricated and are expected to be applied in photocatalysis. In this work, we employ hybrid density functional theory to investigate HfS2 -based van der Waals (vdW) heterojunctions for highly efficient photovoltaic and photocatalytic applications. HfS2 /h-BN and HfS2 /g-C3 N4 heterostructures with direct bandgaps and efficient charge separation are both typical type-II semiconductors and have potential as photovoltaic structures for solar power. Moreover, compared with h-BN and g-C3 N4 single-layers, HfS2 /h-BN heterostructures with 6% tensile strain and HfS2 /g-C3 N4 heterostructures with 9% tensile strain have moderate bandgaps, whose optical absorption is obviously enhanced in the ultraviolet-visible (UV-VIS) light range and whose bandedges are suitable for photocatalytic water splitting. HfS2 /h-BN heterostructures with 6% applied strain, being different from HfS2 /g-C3 N4 heterostructures with 9% strain, possess a direct bandgap and show complete separation of the photoinduced electron–hole pairs. Thus the HfS2 /h-BN heterojunction with 6% strain has bright prospects for use in visible light photocatalytic water splitting to produce hydrogen.